Effect of Dietary Supplementation with Cyphostemma Digitatum on Serum Lipid Profile and Liver Enzymes in Hyperlipidemic Subjects - Al-Duais, Mohammed A; Nogaim, Qais A; Al-Awthan, Yahya S; Al-Dherasi, Aisha (International Journal of Medical and Health Sciences Research, 2014)
Aims: To examine the effects of the administration of CD on lipid metabolism and liver enzymes in hyperlipidemic subjects. Study design: 20 subjects were divided into two groups, each containing ten subjects. Each subject in the 1st group ingested 1g, while the subject in the 2nd group ingested 2g of CD powder as a broth suspension in a single daily dose before lunch during the follow up period of one month. Patients kept their individual diet relatively constant. Methodology: We included 20 hyperlipidemic volunteers (men; age range 20-50 years) of a total of 80 subjects. Blood samples were taken and analyzed for total cholesterol (TC), triglycerides (TG), high density lipoprotein cholesterol (HDL-C), Low density lipoprotein cholesterol (LDL-C), atherogenic index (AI), serum aspartate aminotransferase (AST), alanine aminotransferase (ALT), and alkaline phosphatase (ALP). Results: The results of the present study show a significant decrease in the levels of TC, LDL-C and TG in 1g and 2g of CD administration groups by 12.6, 24.1, 17.1% and 19.9, 25.5 23.4% respectively while the level of HDL-C was significantly increased by 45.6 and 32.5% in 1g and 2g respectively. The atherogenic index (AI) was significantly decreased in 1g and 2g groups by and 47.4% and 45.5% respectively. Our results also show that, CD administration in 1g and 2g subjects causes a significant decrease in ALT and AST by 39.2, 32% and 48.5, 33.3% respectively while the level of ALP was non-significantly decreased. Conclusion: dietary supplementation with CD administration decreased serum lipid profile and liver enzymes in hyperlipidemic subjects. Therefore, it may be regarded as a useful therapy for hyperlipidemia and liver disease. However, further studies are required to compare it with other medicinal plants and with lipid lowering drugs. Place and Duration of Study: Department of Chemistry, Ibb University, Yemen, between February to June 2012.